2019
DOI: 10.1074/jbc.ra118.006472
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes virulence factors, including listeriolysin O, are secreted in biologically active extracellular vesicles

Abstract: Outer membrane vesicles produced by Gram-negative bacteria have been studied for half a century but the possibility that Gram-positive bacteria secrete extracellular vesicles (EVs) was not pursued until recently due to the assumption that the thick peptidoglycan cell wall would prevent their release to the environment. However, following their discovery in fungi, which also have cell walls, EVs have now been described for a variety of Gram-positive bacteria. EVs purified from Gram-positive bacteria are implica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(103 citation statements)
references
References 72 publications
3
100
0
Order By: Relevance
“…Extracellular vesicles, which are delimited by a lipid bilayer and cannot replicate, are naturally released from the cells by many different organisms (50), including S. aureus . Coelho et al found that the composition of extracellular vesicles from the gram-positive bacterial pathogen Listeria monocytogenes , grown in Brain Heart Infusion broth supplemented with 10% bovine fetal serum, were enriched in PE, sphingolipids and triacylglycerols (51). Although it is possible that serum lipids can cross the cell wall in the other direction and insert into the membrane, the fact that Triton X-100 can effectively remove these lipids make this hypothesis less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles, which are delimited by a lipid bilayer and cannot replicate, are naturally released from the cells by many different organisms (50), including S. aureus . Coelho et al found that the composition of extracellular vesicles from the gram-positive bacterial pathogen Listeria monocytogenes , grown in Brain Heart Infusion broth supplemented with 10% bovine fetal serum, were enriched in PE, sphingolipids and triacylglycerols (51). Although it is possible that serum lipids can cross the cell wall in the other direction and insert into the membrane, the fact that Triton X-100 can effectively remove these lipids make this hypothesis less likely.…”
Section: Discussionmentioning
confidence: 99%
“…Performing mock extractions with killed organisms did not isolate EVs [30]. Lipid composition of EVs is different from the lipid bilayer it originates from, observed when comparing EVs with the plasma membrane of whole cells in Gram-positive bacteria Listeria monocytogenes or Streptococcus [30][31][32] as well as when comparing EVs with the outer membrane of Gram-negative bacteria [33]. The same is found for RNA cargo, where RNA cargo does not reflect the RNA content of intact cells, which is highly suggestive of selective enrichment [31].…”
Section: Vesicles Are Artifacts Of Lipid Self-aggregation or Debris Fmentioning
confidence: 99%
“…These populations of EVs are often distinguished based on their biogenesis, size, content, and function [1,8,9]. In addition to these EV types, other vesicles have been reported including; oncosomes, large oncosomes (1-10 µm) [10,11], matrix vesicles [12][13][14], migrasomes (50 nm to 3 µm) [15,16], exopheres (~4 µm), exomeres (~35 nm), and bacterial outer membrane vesicles (OMV) [4,[17][18][19]. Since EVs are heterogeneous populations, there is no unanimous consensus on the nomenclature of them.…”
Section: Introductionmentioning
confidence: 99%